Pengembangan Media Pembelajaran pada Kompetensi Dasar Membaca Gambar Menerapkan Sistem Koordinat Berbasis Adobe Flash - Rika Dewi Indriyani; Tiwan Tiwan; Dwi Rahdiyanta (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This research aimed to design and assess the feasibility of Adobe Flash aided learning media for CNC Turning subject, specifically for the coordinate system topic. The research was a research and development study using the Four-D models of development. Four-D model consists of 4 steps, namely define, design, develop, and disseminate. The instrument being used on this research was closed questionnaires with 4 choices Likert scale. The questionnaires were validated by expert evaluation. Data were collected from the 32 respondents. Data, which were quantitative and qualitative, were analyzed using descriptive analysis technique. The result shows that the learning media meets the teachers' and students' needs and expectation. For the feasibility level, the contents expert gave an average score of 3.37 which can be categorized as "very good". The expert in media gave an average score of 3.45 which is in the "very good" category. The Teacher of the respective subject gave an average score of 3.38 and is categorized as "very good". Students respond well with a score of 3.47 were given, which can be categorized as "very good". Tujuan penelitian ini adalah merancang media pembelajaran berbantuan adobe flash untuk mata pelajaran CNC Turning dengan sistem koordinat. Penelitian ini merupakan penelitian pengembangan dengan model pengembangan Four-D Models yang terdiri dari 4 tahap yaitu define, design, develop, dan disseminate. Instrumen yang digunakan berupa angket dengan skala Likert 4 pilihan jawaban. Angket divalidasi oleh ahli evaluasi. Pengambilan data dilakukan kepada 32 responden. Data kualitatif dan kuantitatif yang diperoleh dianalisis menggunakan teknik analisis deskriptif. Hasil penelitian menunjukkan bahwa media pembelajaran yang dikembangkan telah disesuaikan dengan kebutuhan dan tuntutan dari guru dan siswa. Tingkat kelayakan media pembelajaran menurut ahli materi mendapatkan rerata nilai sebesar 3,37 dengan kategori "sangat baik". Hasil validasi ahli media memperoleh rerata nilai sebesar 3,45 dengan kategori "sangat baik". Hasil validasi guru pengampu memperoleh rerata nilai sebesar 3,38 dengan kategori "sangat baik". Berdasarkan penilaian respon siswa diperoleh rerata sebesar 3,47 dengan kategori "sangat baik".